Identifying the Common Component in International Economic Fluctuations : A New Approach - Lumsdaine, Robin; Prasad, Eswar (Washington, D.C. : International Monetary Fund, 1999)
This paper develops an aggregation procedure using time-varying weights for constructing the common component of international economic fluctuations. The methodology for deriving time-varying weights is based on some stylized features of the data documented in the paper. The model allows for a unified treatment of cyclical and seasonal fluctuations and also captures the dynamic propagation of shocks across countries. Correlations of individual country fluctuations with the common component provide evidence of a 'world business cycle' and a distinct European common component. The results suggest that macroeconomic fluctuations have become more closely linked across industrial economies in the post-Bretton Woods period.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet